Changes in platelet and leukocyte parameters during pregnancy in women with spontaneous pre-term delivery. / Cambios en los parámetros plaquetarios y leucocitarios durante el embarazo en mujeres con parto prematuro espontáneo - Xu, Rongli; Wu, Baohua; Chen, Jinghua; Yan, Jianying (Investigación Clínica, 2020)
Abstract. This study analyzed, retrospectively, the changes of platelet and leukocyte parameters in pregnant women with spontaneous preterm birth. A group of 1050 single embryo pregnant women, who underwent regular obstetric examination and in-patient delivery, were divided into three groups: a preterm birth group, a threatened preterm birth group (at admission) and a full-term group. The platelet parameters [platelet count (PLT), mean platelet volume (MPV), plateletcrit (PCT), platelet distribution width (PDW)] and leukocyte parameters [white blood cell count (WBC), neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR)] were compared in each group. PLT and MPV in preterm birth women were higher than those in the full-term and threatened preterm birth group. Throughout pregnancy, the platelet count showed the lowest level at delivery. The NLR in the preterm group was higher than in the full-term and threatened preterm groups at admission, and the PLR was higher than in the full-term group. The NLR increased gradually during pregnancy, and reached its peak in the full-term group one week before delivery. NLR in the threatened preterm group and preterm group reached their peak in late pregnancy. A BP (back propagation) artificial neural network model was constructed with significant PLT, MPV, NLR and PLR as input values in a univariate analysis. The AUC for predicting the risk of preterm birth using the ROC curve evaluation model was 0.819. In conclusion, the elevation of PLT, MPV, NLR and PLR in pregnant women is related to spontaneous preterm birth. The BP artificial neural network model has certain predictive value for spontaneous preterm birth.Resumen.Este estudio analizó retrospectivamente los cambios de parámetros plaquetarios y leucocitarios en mujeres embarazadas con parto prematuro espontáneo. Un grupo de 1050 mujeres embarazadas con un solo embrión, quienes se sometieron a exámenes obstétricos regulares y a un parto intrahospitalario, se dividieron en tres grupos, de acuerdo a la fecha del trabajo de parto: un grupo prematuro, un grupo de amenaza de parto prematuro (en la admisión) y un grupo a término. Los parámetros plaquetarios [cuenta plaquetaria (PLT), volumen medio plaquetario (MPV), plaquetocrito (PCT), ancho de distribución plaquetaria (PDW)] y parámetros leucocitarios [cantidad de glóbulos blancos (WBC), relación de neutrófilos a linfocitos (NLR), relación de linfocitos a monocitos (LMR), relación de plaquetas a linfocitos (PLR)] se compararon en cada grupo. La PLT y el MPV en las mujeres del grupo prematuro fueron más altos que en las mujeres con amenaza de parto prematuro y el grupo a término. Durante todo el embarazo, la cuenta plaquetaria mostró su nivel más bajo durante el parto. La NLR durante la admisión, fue mayor en el grupo prematuro que en los grupos de parto amenazado prematuro y a término; la PLR fue mayor en el grupo prematuro que en el grupo a término. La NLR aumentó gradualmente durante el embarazo y alcanzó el pico en el grupo a término una semana antes del parto. La NLR alcanzó el pico en los grupos prematuro y amenazado al final del embarazo. Se construyó un modelo de red neuronal artificial de retropropagación (BP) con PLT, MPV, NLR y PLR significativos como valores de importación en el análisis univariado. El AUC (área bajo la curva), utilizando el modelo de evaluación de curva ROC para predecir el riesgo de parto prematuro, fue de 0,819. En conclusión, la elevación de PLT, MPV, NLR y PLR en mujeres embarazadas está relacionada con el parto prematuro espontáneo. El modelo de red neuronal artificial BP tiene cierto valor predictivo para el parto prematuro espontáneo.